Eosinophil extracellular vesicles and DNA traps in allergic inflammation - Weihrauch, Tobias; Melo, Rossana C.N.; Vöhringer, David; Vöhringer, David; Weller, Peter F.; Raap, Ulrike (Frontiers in Allergy, 2024)
Eosinophil granulocytes, a specialized subset of white blood cells, have traditionally been associated with allergic responses and parasitic infections. However, recent research has unveiled their versatile roles in immune regulation beyond these classical functions. This review highlights the emerging field of eosinophil biology, with a particular focus on their release of extracellular vesicles (EVs) and extracellular DNA traps (EETs). It further explores potential implications of eosinophil-derived EVs and EETs for immune responses during inflammatory diseases. The release of EVs/EETs from eosinophils, which also affects the eosinophils themselves, may influence both local and systemic immune reactions, affecting the pathophysiology of conditions such as airway inflammation, chronic rhinosinusitis and atopic dermatitis.
CRIS-Team Scopus Importer:2024-09-06
Keywords: EETosis; eosinophil activation; eosinophilic diseases; extracellular vesicles; inflammation; sombrero vesicles